Perspectives on Nuclear Medicine for Molecular Diagnosis and Integrated Therapy - Kuge, Yuji; Shiga, Tohru; Tamaki, Nagara; Kuge, Yuji; Shiga, Tohru; Tamaki, Nagara (Cham Springer Nature, 2016)
nuclear medicine; diagnostic radiology
English
Keywords: Medical equipment & techniques; nuclear medicine; diagnostic radiology